THE ROLE OF ECOLOGICAL CERTIFICATION IN ENHANCING CORPORATE VALUE AND SUSTAINABLE PERFORMANCE (International journal of artificial intelligence, 2026)
This study examines the economic and operational implications of ecological certification for enterprises. By analyzing market valuation effects, investor responses, and operational performance improvements, it demonstrates how environmental standards such as ISO 14001 and Voluntary Environmental Certifications contribute to sustainable corporate growth. Empirical evidence highlights that certification enhances financial performance, market access, and stakeholder trust, particularly for small and medium-sized enterprises and firms in environmentally sensitive industries. The study also considers challenges including greenwashing and governance issues, emphasizing the importance of rigorous implementation.